PERSEPSI MASYARAKAT PEDESAAN TERHADAP PENDIDIKAN TINGGI (STUDI ANALISIS TEORI GEORGE HERBERT MEAD) - Hukama, Ardika Fateh (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2017)
This study aims to: 1) find out the formal education level of Banjarsari Village, Ngronggot Subdistrict, Nganjuk Regency, 2) find out the perceptions of Banjarsari Village, Ngronggot Subdistrict, Nganjuk Regency towards higher education, 3) find out the meaning of rural community perceptions of higher education with theoretical concepts George Herbert Mead. This type of research is descriptive qualitative, which is describing and interpreting existing data to describe reality in accordance with the actual phenomenon. The results of this study indicate that: 1) the formal education level of the Banjarsari Village community is still low, where elementary school education is 612 people with a percentage of 22.18%, junior high school as many as 739 people with a percentage of 26.78%, high school as many as 1094 people with a percentage of 39.65 %, Colleges as many as 142 people with a percentage of 5.14%, and not as many as 172 with a percentage of 6.23%, 2) the perceptions of rural communities in the village of Banjarsari towards tertiary education are quite good, but to realize their children go on to college less, 3) the relevance of the perceptions of rural communities in higher education and the concept of George Herbert Mead's theory, can be seen from internal factors, namely the economic level and educational background of parents, while external factors, namely the environment.Keywords: Rural Society; Higher education; George Herbert Mead's theory